Optimizing Elementary School Teachers' Knowledge Through Digital Teaching Material Assistance: An Implementative Study - Mardhatillah, Mardhatillah; Kusumaningrum, Shirly Rizki; Anggraini, Ade Eka; Rahayuningsih, Sri; Faizah, Siti (Teunuleh Publisher, 2025)
This study aimed to optimize the pedagogical knowledge and digital skills of elementary school teachers through a Digital Teaching Material (DTM) mentoring program. Using a descriptive qualitative approach, this implementation study was conducted in three stages: needs identification, training and mentoring, and evaluation of results. The research subjects were elementary school teachers selected based on their active program involvement. Results showed significant improvements in technological mastery (26% to 87%), creativity in preparing DTMs (21% to 92%), and student participation (53% to 89%). Mentoring served as effective scaffolding to enhance teachers’ confidence in using technology. Constraints included limited infrastructure and the need for advanced training. This study recommends a sustainable mentoring model to systematically accelerate technology integration in basic education.